Knowledge, Attitude, and Practice of Evidence-Based Medicine among Emergency Doctors in Kelantan, Malaysia - Mohd Ghouse Ahmad Ghaus (MDPI AG, 2021)
This study aimed to determine the prevalence of high levels of knowledge, positive attitude, and good practice on evidence-based medicine (EBM) and identify the associated factors for practice score on EBM among emergency medicine doctors in Kelantan, Malaysia. This cross-sectional study was conducted in government hospitals in Kelantan. The data were collected from 200 emergency physicians and medical officers in the emergency department using the Noor Evidence-Based Medicine Questionnaire. Simple and general linear regressions analyses using SPSS were performed. A total of 183 responded, making a response rate of 91.5%. Of them, 49.7% had a high level of knowledge, 39.9% had a positive attitude and 2.1% had good practice. Sex, race, the average number of patients seen per day, internet access in workplace, having online quick reference application, and attitude towards EBM were significantly associated with EBM practice scores. It is recommended that appropriate authorities provide emergency doctors with broader access to evidence resources. EBM skill training should be enhanced in the current medical school curriculums.